Tuberculin Skin Test and Boosted Reactions among Newly Employed Healthcare Workers: An Observational Study - Kim, Song Yee (Public Library of Science, 2013)
OBJECTIVE: To evaluate the prevalence of and factors associated with latent tuberculosis infection (LTBI) based on the tuberculin skin test (TST) and to estimate the boosted reaction rate among newly employed healthcare workers (HCWs). DESIGN: Newly employed HCWs between January 2010 and July 2012 at Severance Hospital in South Korea were enrolled in this study. A one-step TST was conducted before October 2011, and a two-step TST after October 2011. RESULTS: Of 2132 participants, 778 (36.5%) had positive TST results. Being older (odds ratio [OR] 1.10, 95% confidence interval [CI] 1.06–1.13, P<0.001), male (OR 1.78, 95% CI 1.21–2.62, P = 0.003), rejoining the hospital workforce (OR 1.58, 95% CI 1.04–2.40, P = 0.032), and having a previous history of tuberculosis (TB) (OR 18.21, 95% CI 2.15–154.10, P = 0.008) during the one-step period, and being older (OR 1.15, 95% CI 1.10–1.21, P<0.001) during the two-step period were significantly associated with a positive TST. A two-step TST was performed in 556 HCWs, and a boosted reaction was observed in 79 (14.2%). The induration size on the first TST (5–9-mm group) was the only factor associated with a boosted reaction on the second TST. CONCLUSIONS: The prevalence of LTBI based on the TST among newly employed HCWs was high. The boosted reaction rate on two-step TST was not low; therefore, the use of two-step TST may be necessary for regular monitoring in countries with an intermediate TB burden and a high rate of Bacillus Calmette-Guérin vaccination.